Teachers Professional Competence Assessment Technology in Qualification Improvement Process - Drovnikov, Aleksander S.; Nikolaev, Evgeni L.; Afanasev, Anton S.; Ivanov, Vladimir N.; Petrova, Tatyana N.; Tenyukova, Galina G.; Maksimova, Natalia L.; Povshednaya, Faina V. (International Review of Management and Marketing, 2016)
Scientific and methodological validity of diagnostic procedures and techniques for the study of teachers’ professional competence is designed to ensure the efficiency and dynamism of education management, early detection of possible professional deformations and its correction in the qualification improvement training and in the process of personal and professional self-development. In this regard, this article is focused on the development of technologies to assess the teachers’ professional competence in the process of their qualification’s improvement process. The leading method in the development of this technology are the analysis of the scientific and methodological literature and practical experience which allow reveal its core elements: the tasks of diagnosis, the entities of diagnosis, a set of procedures based on the principles of system-structured pedagogical diagnostics, means and diagnostic tools. In the article the main components and their qualitative indicators to assess the development of teachers’ professional competence in the process of qualification improvement process are proposed. Article submissions are of practical value for managers of teachers’ qualification improvement training courses when evaluating their professional competence. Keywords: technology, estimation, diagnostic techniques, qualification improvement training, professional competence. JEL Classifications: A22, I23, Z39